Impact of a non‐fluoridated microcrystalline hydroxyapatite dentifrice on enamel caries progression in highly caries‐susceptible orthodontic patients: A randomized, controlled 6‐month trial. Issue 2 (30th January 2019) - Schlagenhauf, Ulrich; Kunzelmann, Karl‐Heinz; Hannig, Christian; May, Theodor W.; Hösl, Helmut; Gratza, Mario; Viergutz, Gabriele; Nazet, Marco; Schamberger, Sebastian; Proff, Peter
Abstract: Aim: The aim of the present randomized, controlled trial was to compare the impact of the regular use of a fluoride‐free microcrystalline hydroxyapatite (HAP) dentifrice and a 1400 ppm fluoride control dentifrice on caries progression in 150 highly caries‐active orthodontic patients. Methods: The primary outcome was the occurrence of lesions with International Caries Detection and Assessment System (ICDAS) ≥code 1 on the vestibular surfaces of teeth 15‐25 within 168 days after fixation of orthodontic brackets. Secondary outcomes were lesion development ICDAS ≥code 2, the plaque index, and the gingival index. Results: In total, 147 patients were included in the intent‐to‐treat (ITT) analysis; 133 finished the study per protocol (PP). An increase in enamel caries ICDAS ≥code 1 was observed in 56.8% (ITT) and 54.7% (PP) of the HAP group participants compared with 60.9% (ITT) and 61.6% (PP) of the fluoride control group. Non‐inferiority testing (ITT and PP) demonstrated the absence of a significant difference between the groups. No significant differences in secondary outcomes were observed between the groups. Conclusion: In highly caries‐active patients, the impact of the regular use of a microcrystalline HAP dentifrice on caries progression is not significantly different from the use of a 1400 ppm fluoride toothpaste (ClinicalTrials.gov: NCT02705456).